2015
DOI: 10.1055/s-0034-1399794
|View full text |Cite
|
Sign up to set email alerts
|

Reflux Laryngitis: Correlation between the Symptoms Findings and Indirect Laryngoscopy

Abstract: Introduction The indirect laryngoscopy has an important role in the characterization of reflux laryngitis. Although many findings are nonspecific, some strongly suggest that the inflammation is the cause of reflux. Objective The aim of this study was to evaluate the correlation between reflux symptoms and the findings of indirect laryngoscopy. Methods We evaluated 27 patients with symptoms of pharyngolaryngeal reflux disease. Results Laryngoscopy demonstrated in all patients the presence of hypertrophy of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…In analysing the individual symptoms from RSI versus laryngeal finding from RFS with both statistical method and ICC reliability, this study revealed the symptom hoarseness and frequent throat clearing was positively correlated with posterior commissure hypertrophy, and vocal folds and diffuse laryngeal edema, and these results were almost comparable with the findings of other studies [13,14], karakaya NE et al [15]. Whom used a rigid laryngoscope in their study, they found the posterior commissure hypertrophy was most frequent finding in voice related complaints patients, and RFS was with relatively high intra-rater and inter-rater agreement for evaluation of LPR, while RSI was considerably correlated with both sum RFS and all individual variables from RFS, except posterior commissure hypertrophy.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In analysing the individual symptoms from RSI versus laryngeal finding from RFS with both statistical method and ICC reliability, this study revealed the symptom hoarseness and frequent throat clearing was positively correlated with posterior commissure hypertrophy, and vocal folds and diffuse laryngeal edema, and these results were almost comparable with the findings of other studies [13,14], karakaya NE et al [15]. Whom used a rigid laryngoscope in their study, they found the posterior commissure hypertrophy was most frequent finding in voice related complaints patients, and RFS was with relatively high intra-rater and inter-rater agreement for evaluation of LPR, while RSI was considerably correlated with both sum RFS and all individual variables from RFS, except posterior commissure hypertrophy.…”
Section: Discussionsupporting
confidence: 82%
“…The most frequent symptom detected in this study was hoarseness, followed by the frequent throat clearing, and usually at morning, and this observation was supported by some studies that found dysphonia being a major symptom of LPR, and is more common in morning was due to vocal cords edema that resultant from reflux of gastric acid at supine position night sleep and thus improving during the day time [12], and the most common laryngoscopic physical findings were posterior commissure hypertrophy and vocal cords edema and diffuse laryngeal edema, and these observations were agreed by other studies [13,14].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations